Is There Evidence of FDI Spillover on Chinese Firms' Productivity and Innovation? - Galina Hale; Cheryl Long (Yale University, Economic Growth Center, 2007)
We review previous literature on productivity spillovers of foreign direct investment (FDI) in China and conduct our own analysis using a crosssection of firm data. We find that the evidence of FDI spillovers on the productivity of Chinese domestic firms is mixed, with many positive results largely due to aggregation bias or failure to control for endogeneity of FDI. Attempting over 2500 specifications which take into account forward and backward linkages, we find no evidence of systematic positive productivity spillovers from FDI. We do, however, find robust evidence that Chinese private firms tend to invest less in innovation in the presence of FDI. Combined with our previous findings that domestic private firms tend to be more involved in providing inputs and intermediary goods for foreign firms (Hale and Long, 2006), these results suggest a more passive role played by domestic firms in the global division of labor than envisioned by the Chinese government.
Keywords: L33; F23; O17; 330; FDI spillovers; institutions; SOE; privatization; China